2022
DOI: 10.1177/26331055221109254
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Paradoxically Reduces Cerebral Blood Flow in Alzheimer’s Disease Mice

Abstract: Vascular dysfunction plays a critical role in the development of Alzheimer’s disease. Cerebral blood flow reductions of 10% to 25% present early in disease pathogenesis. Vascular Endothelial Growth Factor-A (VEGF-A) drives angiogenesis, which typically addresses blood flow reductions and global hypoxia. However, recent evidence suggests aberrant VEGF-A signaling in Alzheimer’s disease may undermine its physiological angiogenic function. Instead of improving cerebral blood flow, VEGF-A contributes to brain capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Interestingly, it has been demonstrated that AD patients also express higher levels of VEGF within certain cerebral tissue regions (Ali et al., 2022 ; Mahoney et al., 2021 ; Thomas et al., 2015 ), while cerebral capillary specific expression of VEGF is depleted within AD patients (Provias & Jeynes, 2014 ), which coincides with our in vitro and in vivo results. Additionally, cerebral VEGF overexpression within the AD brain has been linked to pericyte loss, capillary stalls, increases in BBB permeability, decreased CBF and increased AD pathology (Ali & Bracko, 2022 ; Mahoney et al., 2021 ), indicating a maladaptive overexpression. It is becoming more accepted that aberrant VEGF/VEGFR2 signaling plays a large role within promoting AD pathology and cognitive decline and this study has begun to demonstrate that this maladaptive VEGF/VEGFR2 signaling, typical in dementia, may be exacerbated within Tg2576 mice with Hhcy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that AD patients also express higher levels of VEGF within certain cerebral tissue regions (Ali et al., 2022 ; Mahoney et al., 2021 ; Thomas et al., 2015 ), while cerebral capillary specific expression of VEGF is depleted within AD patients (Provias & Jeynes, 2014 ), which coincides with our in vitro and in vivo results. Additionally, cerebral VEGF overexpression within the AD brain has been linked to pericyte loss, capillary stalls, increases in BBB permeability, decreased CBF and increased AD pathology (Ali & Bracko, 2022 ; Mahoney et al., 2021 ), indicating a maladaptive overexpression. It is becoming more accepted that aberrant VEGF/VEGFR2 signaling plays a large role within promoting AD pathology and cognitive decline and this study has begun to demonstrate that this maladaptive VEGF/VEGFR2 signaling, typical in dementia, may be exacerbated within Tg2576 mice with Hhcy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] Furthermore, VEGF-A signaling contributes to leukocyte stalling in brain capillaries and reduces cerebral blood flow in a mouse model of AD. [ 36 ] Conversely, upregulation of VEGF expression has been shown to enhance neurotransmission, synaptic plasticity mechanisms, and neurogenesis. [ 37 ] Multiple studies have suggested that inhibition of EGFR can improve astrogliosis, augment autophagy, alleviate Aβ toxicity and neuroinflammation, and promote axonal regeneration following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org angiogenic functions, leading to cerebral capillary stasis and reductions in blood flow as a presumed mechanism of accelerated cognitive decline (Ali and Bracko, 2022). These pieces of evidence point to the hypothesis that age-related changes in the vascular system are linked to chronic neuroinflammation, progressive deleterious impact on cognitive functions and neuronal death.…”
Section: Neuroinflammation and Immunosenescence In Alzheimer´s Diseasementioning
confidence: 96%